Transición del sistema de gestión de seguridad y salud ocupacional basado en OHSAS 18001:2007 a los lineamientos de ISO 45001:2018 para la unidad San Cristóbal – Minera Bateas - Ollachica Mamani, Karla Noemi (2020)
The purpose of this research work is to transition the occupational health and safety management system based on the OHSAS 18001 standard to the guidelines of the ISO 45001 standard in the San Cristóbal - Minera Bateas Unit, for this purpose established as an initial objective to carry out a situational diagnostic study that allowed identifying the requirements not yet implemented in the recent standard, based on this, the requirements were fully developed as a second objective, to finally assess the effectiveness of the regulatory transition as a third objective . For the scope, all the processes developed in the organization were determined from the exploration, exploitation and processing of minerals for the production of lead and zinc concentrates. The research problem was based on the future outdating of the OHSAS 18001 standard, so the organization seeks to align with the regulatory requirements of ISO 45001 in order to maintain its certification in occupational health and safety, for this purpose it was used The PHVA methodology for continuous improvement, which began with the planning of activities with an implementation schedule, according to that all the requirements of the standard were met, which were evaluated with an internal audit in order to take actions for improvement of process. The research paper concludes that the transition of the Occupational Health and Safety Management System of Minera Bateas was effective, evidenced in the results of the audits carried out, such as the internal one to verify compliance with the ISO 45001 standard and the external audit for the Certification achievement.